The Trajectory of the Jihad Discourse in Malay World: An Analysis on the Baḥr Al-Mādhī by Muḥammad Idrīs Al-Marbawī - Muhammad Adam Abd. Azid; Ibrahim Adham Mohd Rokhibi; Mohd Farhan Md Ariffin; Muhammad Ikhlas Rosele; Mohammad Fahmi Abdul Hamid (Al-Jami'ah: Journal of Islamic Studies, 2022)
The term of jihad has a significant role in the formation of Islamic identity, politics, and nations. For example, the Malay World during the colonial or pre-independence, has created the momentum among community to break free from the colonial at the time. This spirit was injected with elements of jihad through the advice of scholars, graduates returning from the middle east who brought the spirit of independence and through writing. Among the writings that may have a role in explaining jihad among the Malay community is Baḥr al-Mādhī [1924-1960]. This article will analyse on the representation of jihad and warfare term in the Baḥr al-Mādhī, a book written by Muḥammad Idrīs al-Marbawī [1896-1989]. It can be considered as one of the greatest masterpieces of Malay Muslim scholar in the twentieth century. It was composed as a commentary to the hadith in Jāmi‘ al-Tirmidhī and have been written in Malay language. This article also analyses al-Marbawi’s contribution to Malay community understanding jihad in pre independence period of Malaysia through his commentary and translation of the hadith of jihad in Baḥr al-Mādhī. This study applied qualitative study, data collected by library research and analysed by document analysis methodology. Study found that, the Baḥr al-Mādhī by Muḥammad Idrīs al-Marbawī has played a major role in the understanding of jihad among Malays in pre-independence period. This book symbolizes the local wisdom of the Malay community at the earliest time. This contribution can be understood through the background of the writing of this book, its wide pertinence into society and the content of jihad in it.[Konsep jihad mempunyai peran signifikan dalam pembentukan identitas keislaman, politik dan kebangsaan. Misalnya seperti dunia Melayu pada masa kolonial atau pra kemerdekaan dimana sarjana muslimnya yang pulang dari belajar di Timur Tengah mendorong masyarakatnya berjuang melawan kolonialisme dan menuntut kemerdekaan melalui tulisan mereka. Salah satu tulisan yang menerangkan konsep jihad dalam masyarakat Melayu adalah Baḥr al-Mādhī. Artikel ini menjelaskan konsep jihad dan perang dalam karya Baḥr al-Mādhī, satu karya terbaik sarjana muslim Melayu abad 20, yang ditulis oleh Muḥammad Idrīs al-Marbawī (1896-1989). Karya ini merupakan komentar terhadap kitab hadist Jāmi‘ al-Tirmidhī yang ditulis dalam bahasa Melayu. Artikel ini juga membahas kontribusi penting al-Marbawī dalam menjelaskan jihad dalam masyarakat Melayu masa pra kemerdekaan. Dengan studi literatur dan analisis dokumen terkait, artikel ini menunjukkan bahwa karya al-Marbawī merupakan simbol dari kearifan lokal masyarakat Melayu pada masa awal. Kontribusi pentingnya terlihat dari luasnya pengaruh dan pendalaman pemahaman tentang jihad di masyarakat Melayu saat itu.]